ADHD Symptoms in a Non-Referred Low Birthweight/Preterm Cohort: Longitudinal Profiles, Outcomes, and Associated Features. Issue 9 (July 2018) - Krasner, Aaron J.; Turner, J. Blake; Feldman, Judith F.; Silberman, Anna E.; Fisher, Prudence W.; Workman, Catherine C.; Posner, Jonathan E.; Greenhill, Laurence L.; Lorenz, John M.; Shaffer, David; Whitaker, Agnes H.
Objective: This study's objective is to differentiate possible ADHD syndromes on the basis of symptom trajectories, prognosis, and associated clinical features in a high-risk cohort.Method: Latent class analysis of inattentive (IA) and hyperactive–impulsive (HI) symptoms in 387 non-disabled members of a regional low birthweight/preterm birth cohort who were evaluated for ADHD at 6, 9, and 16 years. Adolescent functional outcomes and other clinical features were examined across the classes.Results: Three latent classes were identified: unaffected (modest IA and HI symptom prevalences at six, remitting by nine), school age limited (relatively high IA and HI symptom prevalences at six and nine, declining by 16), and persistent inattentive (high IA and HI prevalences at six and nine, with high IA levels persisting to 16). The persistent inattentive class was distinctively associated with poor functioning, motor problems, other psychiatric disorders, and social difficulties as indexed by a positive screen for autism spectrum disorder at 16.Conclusion: These findings differentiate a potential persistent inattentive syndrome relevant to ADHD evaluation and treatment.